Kemal Ahmed Dede''s verse narrative Tercüme-i Menakıb-ı Mevlana (a verse version in The Menâkıbü'l-Ârifîn tradition) - Sinan Nizam, Betül. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
The essential aim of this dissertation is to uncover the life of one of the sixteenth century sufis and poets, Kemâl Ahmed Dede, forgotton among the Mevlevî sources, to present his mesnevi Tercüme-i Menâkıb-ı Mevlânâ which is abridged translation of Menâkıbü‟l-Ârifîn in verse, and to discover his translation aims and methods. In order to achieve this, his menakıpname, his only work for the time being, has been examined in the frames of its form, translation aspects, content and style, then compared with main text if needed. There will be given some brief information about Menâkıbü‟l-Ârifîn, the most important work that describes Mevlânâ‟s and his successors‟ menkıbes in Turkish literature, and its translations and abbreviated retellings in Persian. By doing so, it has been tried to putforward the complete body of the works that includes Tercüme-i Menâkıb-ı Mevlânâ as one of its versions. As a conclusion, this dissertation has approached to the subject not only as an analysis of poet and his work, but also as the context of intertextuality owing to its translation nature and aspects.
Keywords: Sufi poetry, Turkish.; Manuscripts, Turkish -- Turkey.